OBESITY SCREENING AND HEALTH EXAMINATION (BLOOD PRESSURE, HEMOGLOBIN LEVEL AND BLOOD GROUP) IN ADOLESCENTS - Danarsih, Dwi Eni; Artini, Dyah; Purnamaningsih, Nur'Aini (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2023)
Late adolescence is the age at which blood donors are permitted. The government's efforts to recruit voluntary blood donors can actually start at a young age. Unhealthy lifestyles can affect the health of adolescents. Cases of non-communicable diseases in the adolescent age group have increased. For this reason, it is necessary to have early detection of degenerative risk factors as well as blood group data collection in an effort to prepare a generation that is healthy and willing to donate blood. This community service aims to check the obesity status, blood pressure, hemoglobin levels, and blood type of adolescents living in Bener Tegalrejo Village, Yogyakarta. This activity is divided into several stages, namely coordinating with the activity site, preparing tools and materials, socializing the inspection flow, and the implementation stage. The results of this activity are expected to be the beginning of the formation of cooperation partners for recruiting blood donors with PMI. The result of this activity is that most of the youth are in good health and meet the requirements to donate blood.